Reflections on China’s participation in the global governance of cyberspace - Ning WU (网络与信息安全学报)
The current situation of global governance of cyberspace was combed,and the difficulties and challenges were analyzed deeply.Based on the fully understanding of the Chinese international strategy of cooperation on cyberspace,the principles of participation on global governance of cyberspace,which should be paid attention to,were proposed,as well as the measures on leading the establishment of international rules on cyberspace to strive for discourse right and institutional power.